Computer games : 7th Workshop, CGW 2018, held in conjunction with the 27th International Conference on Artificial Intelligence, IJCAI 2018, Stockholm, Sweden, July 13, 2018, Revised Selected Papers /: 7th Workshop, CGW 2018, held in conjunction with the 27th International Conference on Artificial Intelligence, IJCAI 2018, Stockholm, Sweden, July 13, 2018, Revised Selected Papers. (2019) - Unknown
No abstract available